The Behavior of Ammonium Exchange (Q/I) in Soil, Nitrogen and Carbon Uptake, and Mung Beans (Vigna radiata L.) Yields as Affected by Tillage and Fertilization at the Sixth Planting Period in Ultisol Soil - Septi Nurul Aini; Omita Mega Nurtyas; Jamalam Lumbanraja; Abdul Kadir Salam (JOURNAL OF TROPICAL SOILS, 2022)
Ultisol soil has a low organic matter content, CEC, and pH, causing an insufficient buffering capacity for N nutrients, especially NH4+. The objective of this study was to determine the effect of tillage and fertilization on the quantity and intensity (Q/I) of Ammonium (CRNH40, PBCNH4+, NH40, KG) in the soil, plant N and C uptake, and mung bean yields at the sixth growing season in ultisols. This study was arranged in a 2 Ã— 2 factorial in a Randomized Block Design (RBD). The first factor was the tillage system (T), namely minimum tillage (T0) and intensive tillage (T1). The second factor was the fertilization (P), namely without fertilizer application (P0), and with fertilizer application (NPK 200 kg ha-1 + 1 Mg ha-1 chicken manure) (P1). Each treatment was replicated four times. The results showed that the application of NPK fertilizer significantly affected the mung bean yield, mung bean plant Nitrogen and Carbon uptake at harvest time. While, the intensive tillage had a very significant effect on increasing the N uptake compared to the minimum tillage. Minimum tillage and fertilization increased Q/I parameters (PBCNH4+, KG, CRNH40, and NH40). The parameter of Q/I (CRNH40) was significantly correlated with mung bean plant N and C uptake. PBCNH4+ and KG were significantly correlated with mung bean yields.